2019
DOI: 10.5194/acp-2019-985
|View full text |Cite
Preprint
|
Sign up to set email alerts
|

The influence of anomalous atmospheric conditions at Ny-Ålesund on clouds and their radiative effect

Abstract: <p><strong>Abstract.</strong> This study analyses occurrence of events with increased and decreased integrated water vapor (IWV) and atmospheric temperature (T) at the Arctic site Ny-Ålesund and their relation to cloud properties and the surface cloud radiative effect (CRE). For this study, we used almost 2.5 years (from June 2016 to October 2018) of ground-based cloud observations processed with the Cloudnet algorithm, IWV and T from microwave radiometer … Show more

Help me understand this report
View published versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

1
1
0

Year Published

2020
2020
2022
2022

Publication Types

Select...
2
1

Relationship

2
1

Authors

Journals

citations
Cited by 3 publications
(2 citation statements)
references
References 55 publications
1
1
0
Order By: Relevance
“…Shupe et al (2011) have analyzed the occurrence and macro-physical properties of Arctic clouds at six observatories, including Ny-Ålesund, and found, for example, that clouds are more persistent at the far western Arctic sites. More detailed analyses of cloud radar observations from Ny-Ålesund (Nomokonova et al, 2019b;Ebell et al, 2020;Nomokonova et al, 2019a;Gierens et al, 2020) partly confirmed results of previous studies, e.g. high a cloud occurrence at Ny-Ålesund in summer and autumn, but also revealed differences.…”
Section: Site Descriptionsupporting
confidence: 86%
“…Shupe et al (2011) have analyzed the occurrence and macro-physical properties of Arctic clouds at six observatories, including Ny-Ålesund, and found, for example, that clouds are more persistent at the far western Arctic sites. More detailed analyses of cloud radar observations from Ny-Ålesund (Nomokonova et al, 2019b;Ebell et al, 2020;Nomokonova et al, 2019a;Gierens et al, 2020) partly confirmed results of previous studies, e.g. high a cloud occurrence at Ny-Ålesund in summer and autumn, but also revealed differences.…”
Section: Site Descriptionsupporting
confidence: 86%
“…Microwave radiometer retrievals are available in Nomokonova, Ritter, and Ebell (2019) (for the 2017–2018 period), and in Ebell and Ritter (2022) (for the 2019–2021 period). The Cloudnet target classification product can be downloaded from https://cloudnet.fmi.fi/.…”
Section: Data Availability Statementmentioning
confidence: 99%